Выбор аппаратов защиты по условию предупреждения перегрева кабельных изделий - Aushev Игорь (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The methods of selection of protection devices according the condition of prevention against overheating of cables are presented. Selected according the rule of electrical installations, the protection device is testing on coordination in functioning with wire&cable (W&C). By means of combination of time and current characteristics of protection devices and W&C the fire safety of cabling is analyzed.